Predictive control of pore architecture in ice-templated scaffolds via heat flux density modulation - Gengyao Wei; Ruth E. Cameron; Serena M. Best (Materials Today Advances, 2024)
Replicating the intricate architecture of native tissues remains a significant challenge in tissue engineering. Ice-templated biomimetic scaffolds possess controlled porosity that conveniently resembles the native parenchyma of many tissues. In this study, we investigate the relationship between the porous architecture of lyophilised collagen scaffolds and key processing parameters during production. We establish a predictive model that correlates specific lyophilisation conditions with the resulting pore sizes. Systematic variations in the freeze-drying conditions resulted in scaffolds with average pore sizes ranging from 46 μm to 251 μm, effectively matching the length scale of extracellular matrix features found in native tissues. We introduce the concept of heat flux density (HFD) at equilibrium as a metric for quantifying latent heat extraction efficiency during the freezing process. Our findings reveal a power law relationship between HFD at equilibrium and pore size, with an exponent of −0.44. This approach provides a non-destructive and non-intrusive method for precisely controlling pore architecture, advancing the potential for creating scaffolds that closely emulate the complex structures of native tissues.